Comparison of an in-house real-time duplex PCR assay with commercial HOLOGIC® APTIMA assays for the detection of Neisseria gonorrhoeae and Chlamydia trachomatis in urine and extra-genital specimens - Venter, Johanna M. E. (BMC Infect Dis, 2019)
BACKGROUND: Extra-genital Neisseria gonorrhoeae and Chlamydia trachomatis infections are mostly asymptomatic, and important reservoir sites of infection as they often go undetected and may be more difficult to eradicate with recommended therapeutic regimens. Commercial nucleic acid amplification tests (NAATs) have not received regulatory approval for the detection of N. gonorrhoeae and C. trachomatis in extra-genital specimens. The HOLOGIC® APTIMA Combo2 assay for N. gonorrhoeae and C. trachomatis has performed well in evaluations using extra-genital specimens. METHODS: We assessed the performance of an in-house real-time duplex PCR assay for the detection of N. gonorrhoeae and C. trachomatis in urine and extra-genital specimens using the HOLOGIC® APTIMA assays as gold standard comparators. Urine, oropharyngeal and ano-rectal specimens were collected from each of 200 men-who-have-sex-with-men (MSM) between December 2011 and July 2012. RESULTS: For N. gonorrhoeae detection, the in-house PCR assay showed 98.5–100% correlation agreement with the APTIMA assays, depending on specimen type. Sensitivity for N. gonorrhoeae detection was 82.4% for ano-rectal specimens, 83.3% for oropharyngeal specimens, and 85.7% for urine; and specificity was 100% with all specimen types. The positive predictive value (PPV) for N. gonorrhoeae detection was 100% and the negative predictive value (NPV) varied with sample type, ranging from 98.5–99.5%. For C. trachomatis detection, correlation between the assays was 100% for all specimen types. The sensitivity, specificity, PPV and NPV of the in-house PCR assay was 100% for C. trachomatis detection, irrespective of specimen type. CONCLUSION: The in-house duplex real-time PCR assay showed acceptable performance characteristics in comparison with the APTIMA® assays for the detection of extra-genital N. gonorrhoeae and C. trachomatis.